Posterior reversible encephalopathy syndrome could be an underestimated variant of “reversible neurological deficits” in Systemic Lupus Erythematosus - Liu, Bin (BioMed Central, 2012)
BACKGROUND: Posterior reversible encephalopathy syndrome (PRES) has been increasingly identified in patients with systemic lupus erythematosus (SLE) owing to the advance in neuroimaging techniques. Prompt diagnosis is pivotal to improve its outcome. To analyze the clinical and radiographic profile of PRES in patients with SLE and search for the appropriate treatment strategy PRES in SLE. METHODS: SLE patients who fulfilled the diagnostic criteria for PRES from August 2008 to January 2011 were evaluated at baseline, and followed to determine clinical outcomes. Data were analysis on clinical characteristics, laboratory abnormalities, treatment details, and outcomes. RESULTS: Ten episodes of PRES in patients with SLE were identified. All patients were female, mean age of onset was 22.93 ± 2.48 years, and SLEDAI at the onset of PRES were 25.8 ± 5.7. All cases had acute onset of headache, altered mental status, stupor, vomiting, cortical blindness and seizures. Neurological symptoms were the initial manifestation of SLE in three cases. Head magnetic resonance imaging (MRI) demonstrated posterior white matter edema involving the parietal, temporal and occipital lobes, which were more conspicuous on T2 weighted spin echo and diffusion-weighted MR imaging (DWI) than on computed tomography (CT) scan. Complete clinical and radiographic recovery was observed in 8 patients after prompt treatment with corticosteroids. CONCLUSIONS: PRES might be due to lupus per se besides other traditional causative factors such as hypertension. PRES might be an underestimated variant of “reversible neurological deficits” in SLE. Prompt recognition and timely management is important to prevent permanent neurological deficits.